PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN KAMPUNG WISATA AIR SUMBER BANTENG DI KELURAHAN TEMPUREJO, KECAMATAN PESANTREN, KOTA KEDIRI - Anggriani, Ema Idha; Eprilianto, Deby Febriyan (Publika, 2023)
Community participation in tourism development activities is a potential thing to do. Through the concept of community participation, it provides several benefits, one of which is increasing the success of development because it is based on the problems and needs of the community. As in the development of Sumber Banteng Water Tourism Village, it is in the process of developing towards tourist attractions. This research aims to describe community participation in the development of Sumber Banteng Water Tourism Village in Tempurejo Village, Pesantren District, Kediri City. The type of research used in this study is descriptive with a qualitative approach. The data source retrieval technique uses purposive sampling technique. While in the focus of this research can be seen from the forms of community participation ranging from the participation of ideas, participation of labor, participation of property, participation of skills and skills, and social participation. The results showed that community participation in the development of Sumber Banteng Water Tourism Village in Tempurejo Village has been running quite well. The participation of the surrounding community from planning to implementation is carried out independently. Then the lack of participation in the form of skills from Pokdarwis so that the skills they have still rely on the efforts of local residents in Sumber Banteng. The obstacles found not only come from community participation, but also come from funds which are an obstacle. Funds obtained only from the procurement of voluntary boxes and other entertainment venues. Keywords: Community participation, Tourism Development, Tourism.